Retinal sensitivity changes after retinal surgery between new onset and long-term rhegmatogenous retinal detachment - Retno Ekantini, Rose Angela Nurini Agni (Universitas Gadjah Mada, 2008)
Background: Rhegmatous retinal detachment is an emergency case which will had to blindness if it is not managed properly. It could managed mostly by surgery. Many factors influence the success of the management.Objective: To know the difference of central retinal sensitivity changes after retinal surgery in new onset and long-term rhegmatogenous retinal detachment (RRD)Methods: A prospective cohort study. Eyes with RRD which showed anatomically successful surgery were included in this study. RRD developed more than 24 days prior to surgery was considered as long-term RRD. Sample size was calculated based on the assumption that clinically significant central retinal sensitivity change was 5 decibels. Central retinal sensitivity was examined with Goldmann manual kinetic perimetry before and 3 months after surgery.Results: There were 35 eyes included in this study, consisted of 19 new onset RRDs and 16 long-term RRDs. The macula were involved in all of the subjects. The extent of retinal detachment ranged between 4 clock hours and 12 clock hours. PVR was found in 4 eyes. Two eyes (5.7%) underwent scleral buckling (SB), one eye (2.9%) underwent SB and posterior vitrectomy using silicone oil, and 32 eyes (91.4%) underwent SB and posterior vitrectomy using gas. Retinotomy was performed in 2 eyes and internal limiting membrane (lLM) peeling in 1 eye. Three months after the surgery, the mean change of central retinal sensitivity for both groups was 8.60 :I: 6.02 dB (range: -3 dB to + 23 dB), the new RRD was 6.9 :I: 5.57 dB, and the long-term RRD (p= 0.067) was 10.63 :I: 6.07 dB.Conclusion: The difference of central retinal sensitivity changes between new onset and long-term RRD was not significant clinically and statistically. However, both groups showed improvement of central retinal sensitivity.Keywords: retinal sensitivity - new onset rhegmatogenous retinal detachment - long-term rhegmatogenous retinal detachment - Goldmann manual kinetic perimeter